Konsep Dasar Pembiayaan Dalam Perbankan Syariah - Juliani Wulandari; Bunga Aura Putri Sulistyono; David Maulana Verdiansyah; Wisanggeni Wahyu Lintang B.S; Renny Oktafia (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Financing can be interpreted as funding provided by one party to another party. Its function is to support investments that will or have been planned by the institution. Financing can also be interpreted as trust or trust. It means that the financing institution as sahib al-mal puts trust in someone to carry out the mandate given. All such costs must be used properly, fairly, and must be accompanied by clear terms and are responsible for all parties. Every Islamic financial institution has a philosophy of seeking the pleasure of Allah SWT. to acquire the virtues of the world and the hereafter. Therefore, any activities of financial institutions that are considered deviant from religious demands should be avoided. In the implementation of financing, Islamic banks must meet two most important aspects. First, the Shar'i aspect where in every realization of financing to customers must remain guided by Islamic Shari'a. Second, the economic aspect which still considers the profit generation for Islamic banks and for customers.